Polypharmacy and potentially inappropriate medications for elder people in gerontological nursing - Marques,Gabrielle Ferreira Melo (2018)
ABSTRACT Objective: To identify polypharmacy and potentially inappropriate medications (PIM) for elder people with chronic health situations and its implications for gerontological nursing. Method: Descriptive and transversal study, conducted from March to September 2016 by pharmaceutical residents in the clinic of Endocrinology of a hospital in Mid-West region of Brazil. Results: 44 elder people with an average age of 69.5 (± 6.79) years old had their assessed prescriptions. We identified 65 medications prescribed 253 times, in which 10 PIM (15.4%) were prescribed 51 times. 33 seniors (72.7%) had at least one PIM, of those, 66.7% were polymedicated. Of the total, 22 elder people (50%) were subjected to polypharmacy and made use of at least one PIM. Conclusion: The results showed high incidence of PIM and polypharmacy, as well as their physiological impacts to the elder population. The study provokes discussions about that the trained nurse in human aging has skills and competencies able to enhance interventions related to pharmacotherapy.